FRoG dose computation meets Monte Carlo accuracy for proton therapy dose calculation in lung. (June 2021) - Magro, Giuseppe; Mein, Stewart; Kopp, Benedikt; Mastella, Edoardo; Pella, Andrea; Ciocca, Mario; Mairani, Andrea
Highlights: GPU-accelerated analytical dose engine (FRoG) established for proton therapy in lung. Dosimetric evaluation of pencil beam algorithm (FRoG) versus RayStation Monte Carlo (RS-MC) using heterogeneous lung phantom. Dose and LETd validated for FRoG against general purpose Monte Carlo (gp-MC) in patients for clinical investigations. FRoG demonstrated prediction power comparable to RS-MC and gp-MC. Abstract: Purpose: To benchmark and evaluate the clinical viability of novel analytical GPU-accelerated and CPU-based Monte Carlo (MC) dose-engines for spot-scanning intensity-modulated-proton-therapy (IMPT) towards the improvement of lung cancer treatment. Methods: Nine patient cases were collected from the CNAO clinical experience and The Cancer Imaging Archive-4D-Lung-Database for in-silico study. All plans were optimized with 2 orthogonal beams in RayStation (RS) v.8. Forward calculations were performed with FRoG, an independent dose calculation system using a fast robust approach to the pencil beam algorithm (PBA), RS-MC (CPU for v.8) and general-purpose MC (gp-MC). Dosimetric benchmarks were acquired via irradiation of a lung-like phantom and ionization chambers for both a single-field-uniform-dose (SFUD) and IMPT plans. Dose-volume-histograms, dose-difference and γ-analyses were conducted. Results: With respect to reference gp-MC, the average dose to the GTV was 1.8% and 2.3% larger for FRoG and the RS-MC treatment planning system (TPS). FRoG and RS-MC showed a local γ-passing rate of 96% and 93%. Phantom measurements confirmed FRoG's high accuracy with a deviation < 0.1%. Conclusions: Dose calculation performance using the GPU-accelerated analytical PBA, MC-TPS and gp-MC code were well within clinical tolerances. FRoG predictions were in good agreement with both the full gp-MC and experimental data for proton beams optimized for thoracic dose calculations. GPU-accelerated dose-engines like FRoG may alleviate current issues related to deficiencies in current commercial analytical proton beam models. The novel approach to the PBA implemented in FRoG is suitable for either clinical TPS or as an auxiliary dose-engine to support clinical activity for lung patients.